Bottensubstratets inverkan på föryngring av Flodpärlmussla - Boström, Viktor; Holm, Hjalmar (SLU/Dept. of Forest Ecology and Management, 2012)
The freshwater pearl mussel (Margaritifera margaritifera) is threatened throughout its range. There has been a substantial decline of the species and one major reason is habitat degradation. We investigated how the substrate composition of the bottom floor affects the regeneration of the mussel by analyzing data from the Västerbotten County Board’s inventory of the freshwater pearl mussel. The results implied that fine material such as fine sediment and sand might be detrimental to regeneration whereas gravel and boulders and in particular stone seem to be beneficial. The reason for this is believed to be that more coarse materials offer a more stable environment and also have a smaller risk of getting the hyporheic zone clogged by siltation which threatens to cut off the supply of oxygen and food for the juvenile mussels. The results can be used in restoration and reintroduction programs.